Water poverty index of municipalities in the State of Tocantins, Brazil - Virgílio Lourenço Silva Neto; Souza, Lucas Barbosa e; Morais, Marco Antonio Vieira (Geografares, 2023)
Water scarcity is a prevalent issue in Brazil, and it is crucial to analyze it at the state level, such as in the case of Tocantins state. This study aims to determine and analyze the conditions of water scarcity in 139 municipalities in Tocantins. Due to the diverse range of information included in this indicator, the values for each subcomponent were normalized using the maximum and minimum values based on the spatial scale. This allowed for a comparative analysis. The weights assigned to the components comprising this index were 1 for resource, access, and capacity, and 0.5 for the use component. These weights were applied in the equation that represents the water poverty index. According to the scale, which ranges from 0 for the most critical situation to 1 for excellent condition, most municipalities in Tocantins, as well as the average of this index for the state, are classified as good. The municipalities with the best conditions were Palmas (0.70), Porto Nacional (0.65), Miracema, and Pedro Afonso (0.63), and Paraíso do Tocantins (0.61), all located in the central portion of the state. On the other hand, municipalities with a high critical index were Praia Norte (0.29), Juarina (0.28), Aragominas (0.27), Piraquê (0.24), and Riachinho (0.22), located in the northern part of the state. The obtained result should not be interpreted as an abundance of water resources, but rather as a favorable combination of factors that enable favorable conditions for resources, access, capacity, utilization, and the environment.